Nephrotic Syndrome Due to Primary Renal Disease in Adults: I. Survey of Incidence in South-east England. Issue 5656 (31st May 1969) - Sharpstone, P.; Ogg, C. S.; Cameron, J. S.
Abstract : In a prospective survey of the nephritic syndrome due to primary renal disease in adult patients in the South-east Metropolitan Region of England 50 patients were seen in a two-year period—a minimum annual incidence of 9·0 new cases per million adult population. The frequency distribution of the three main histological groups was "minimal change" 30%, membranous nephropathy 12%, and proliferative glomerulonephritis 58%. The higher proportion of patients with minimal histological change compared with that found in most previously published series may be explained by the avoidance of selection of patients for inclusion. The much lower incidence of membranous nephropathy probably reflects the use of stricter histological criteria for this diagnosis.